The Essence of Terrorism: We Are Different - Minderop, Albertine (Journal of Terrorism Studies, 2019)
This research entitled: The Essence of Terrorism: We Are Different was written with the aim of showing that a strong belief in an ideology or a religion can lead to the concepts of the self (we) and the other (they). Thought about this concept gave an issue to a sense of difference and animosity towards other parties. This party must be destroyed because "we are different" and the other party is a threat. The research method used is Content Analysis and Hermeneutics Technique. The findings and discussion of this research are the reluctance of certain groups to accept differences related to any ideology and religious beliefs. In addition, there are also stages of attitude: fanatical, exclusive, extreme, radical, and terrorist, which are marked by various attitudes of destruction and annihilation. The conclusion of this research is the view of certain groups who assume that everything they do is the truth. Death is a defense and is a coveted gift.